The Wits Digitisation Experience: Lessons Learned and Suggestions for National Collaboration - Pickover, Michele (My University, 2013)
The presentation will provide a brief background to the Wits Digitisation Centre, the services it delivers and strategies for the sustainability of the Centre. It will discuss our vision for an Integrated Resource Discovery platform for digital resources in the Library as well as digitisation policy development at Wits. Finally, it will allude to some of the technical and intellectual issues that need to be engaged with for collaboration across institutions and a possible way forward for a South African Digital Libraries and Archives Portal will be proposed.
Brief background to the Wits Digitisation Centre.
Keywords: Wits Digitisation Experience